Thermal Imaging and Biometrical Thermography of Humpback Whales - Horton, Travis W.; Oline, Alice; Hauser, Nan; Khan, Tasnuva Ming; Laute, Amelie; Stoller, Alyssa; Tison, Katherine; Zawar-Reza, Peyman (Frontiers in Marine Science, 2017)
Determining species distributions through time and space remains a primary challenge in cetacean science and conservation. For example, many whales migrate thousands of kilometers every year between remote seasonal habitats along migratory corridors that cross major shipping lanes and intensively harvested fisheries creating a dynamic spatial and temporal context that conservation decisions must take into account. Technological advances enabling automated whale detection have the potential to dramatically improve our knowledge of when and where whales are located, presenting opportunities to help minimize adverse human-whale interactions. Using thermographic data we show that near-horizontal (i.e. high zenith angle) infrared images of humpback whale (Megaptera novaeangliae) blows, dorsal fins, flukes and rostrums record similar magnitude brightness temperature anomalies relative to the adjacent ocean surface. Our results demonstrate that these anomalies are similar in both low latitude and high latitude environments despite a ~16°C difference in ocean surface temperature between study areas. We show that these similarities occur in both environments due to emissivity effects associated with oblique target imaging, rather than differences in cetacean thermoregulation. The consistent and reproducible brightness temperature anomalies we report provide important quantitative constraints that will help facilitate the development of transient temperature anomaly detection algorithms in diverse marine environments. Thermographic videography coupled with laser range finding further enables calculation of whale blow velocity, demonstrating that biometrical measurements are possible for near-horizontal datasets that otherwise suffer from emissivity effects. The thermographic research we present creates a platform for the delivery of 3 important contributions to cetacean conservation: 1) non-invasive species-level identifications based on whale blow shapes and velocities recorded by infrared videography; 2) reduced ship-strike rates through automated thermographic cetacean detection systems deployed in high traffic areas; 3) monitoring the spatial and temporal distributions of endangered animals in remote habitats.